Reflexões acerca das contribuições de Heidegger para uma clínica fenomenológica-existencial - Ferreira, Lucyenne Christian Rosas (2010)
The purpose of this dissertation is to emphasize Heidegger s important significance to psychoanalysis clinics stressing phenomenology and hermeneutics, supported by bibliography research on the subject matter The first chapter dwells in existential analysis and a way to understanding the being and not being as a closed pre-established concept system. Definition of the term analysis it it s Greek origin άναλύειν (analisein), meaning extricating an entanglement, in order to free him and through the clients narrative to weave or rebuild his own existence. The second chapter deals with the technicals inside the clinic, under heideggerian perspective, studying this referential. Finally there is a comparative study of Heidegger s thoughts related to the clinic and a bibliographic and historic overview, including Gadamer works and the intrinsic dialogic nature of the clinic and its possibilities.